Pemberdayaan Masyarakat Berbasis Kewirausahaan di Kampung Nolokla Distrik Sentani Timur Kabupaten Jayapura - Roland Everson Binur; Marsal Arung Lamba; Lazarus Ramandei; Ibrahim Kristofol Kendi; Sudiro Sudiro; Juliani Wairata; Tommi Tommi; Rasi Kasi Samosir (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Community empowerment is a concept of economic development that summarizes these social values reflecting the new paradigm of development, namely those that are people-centred, participatory, empowering, sustainable, this concept is broader than merely meeting basic needs or providing mechanisms to prevent further impoverishment processes (safety net), whose thoughts have recently been developed as an effort to find alternatives to the concepts of growth in the past. The concept of Empowerment in the field of Entrepreneurship in Nolokla Village is a form of empowerment that involves the community directly, in order to improve the community's economy in the field of entrepreneurship by utilizing the potential that exists in Nolokla Village. The goal to be achieved in this study is to empower the Nolokla Village Community to be able to be an independent entrepreneur. The method used is descriptive qualitative, with data collection techniques, observation, interviews and documentation, and using data analysis techniques in the form of data reduction, data presentation and conclusion drawing. The results of this study indicate that there is potential that can be developed through community empowerment efforts, especially in the field of business independently.